2009
DOI: 10.1152/ajpregu.00396.2009
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of oat β-glucan and sucrose feedings on infection and macrophage antiviral resistance following exercise stress

Abstract: Oat beta-glucan can counteract the exercise-induced increased risk for upper respiratory tract infection (URTI) in mice, which is at least partly mediated by its effects on lung macrophages. Substantial evidence in humans indicates that carbohydrate-containing sports drinks can offset the decreased immune function associated with stressful exercise. However, no studies in animals or humans have directly examined their effects on URTI using a controlled virus-challenge model. We examined the effects of sucrose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 38 publications
0
22
1
Order By: Relevance
“…Furthermore, there was no reduction of URTI incidence in athletes during 2-week period after intensive exercise. These data contrast with findings from studies investigating the effect of oat b-glucan on immunosuppression in exercised mice (Murphy et al 2004(Murphy et al , 2007(Murphy et al , 2009Davis et al 2004b). It may be related to differences in the ability of oat b-glucan to interact with immune cells through the proximal small intestine in humans.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…Furthermore, there was no reduction of URTI incidence in athletes during 2-week period after intensive exercise. These data contrast with findings from studies investigating the effect of oat b-glucan on immunosuppression in exercised mice (Murphy et al 2004(Murphy et al , 2007(Murphy et al , 2009Davis et al 2004b). It may be related to differences in the ability of oat b-glucan to interact with immune cells through the proximal small intestine in humans.…”
Section: Discussioncontrasting
confidence: 84%
“…The effects of b-glucan supplementation on exercise-induced changes in immune function and upper-respiratory tract symptoms have been investigated in several animal studies (Davis et al 2004a, b;Murphy et al 2004Murphy et al , 2007Murphy et al , 2008Murphy et al , 2009 and in three recent human studies of top-level athletes Talbott and Talbott 2009;Bobovcak et al 2010). In a very recent human study, Nieman et al (2008) investigated the effect of an oat b-glucan supplement on exercise-induced suppression of immune system in athletes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microarray analysis revealed that injection of PP alters gene expression patterns in the silkworm hemocytes and fat body cells, resulting in the induction of genes involved in innate immunity (10). Stimulants of innate immunity are therapeutically effective against viral infection (30)(31)(32)(33)(34). Thus, we hypothesized that activation of PP by GE-3 would contribute to the defense against viral infection in the silkworm.…”
Section: Therapeutic Effect Of Ge-3 Against Viral Infectionmentioning
confidence: 99%
“…Whereas several lines of evidence suggest the effectiveness of polysaccharides in the treatment for viral infectious diseases (30)(31)(32)41), evidence for a relationship between therapeutic effectiveness and stimulation of immunity by polysaccharides is limited. Our results provide new evidence for this relationship.…”
mentioning
confidence: 99%